Leveraging a qualitative data repository to integrate patient and caregiver perspectives into clinical research. Issue 1 (21st July 2021) - Christensen, Vivian; Parker, Kellee; Cottrell, Erika
Abstract: Understanding patient and caregiver experiences is a critical component of the conception, design, and implementation of clinical research studies. The "Database of Individual Patient Experiences" (DIPEx) is an innovative, evidence-based approach for eliciting rich information about health experiences. We conducted a formative evaluation with 14 pediatric oncology researchers to assess the value of using data from a DIPEx study on patient and caregiver experiences with childhood cancer to inform patient-centered research in pediatric oncology. Participants identified barriers to incorporating patient perspectives and experiences into their research and how the DIPEx approach could be leveraged to facilitate this practice.